Localisation of tumour deposits by external scanning after injection of radiolabelled anti-carcinoembryonic antigen. Issue 6209 (26th January 1980) - Dykes, P W; Hine, K R; Bradwell, A R; Blackburn, J C; Reeder, T A; Drolc, Z; Booth, S N
Abstract : Sheep IgG antibody to carcinoembryonic antigen (CEA) was radiolabelled with 131I and used to identify human gastrointestinal tumours by external subtraction imaging. 99Tc-pertechnetate and 99Tc-human serum albumin were used to identify tissue spaces. In 13 patients with tumours four out of five primary sites and eight out of 11 secondary sites were successfully shown. Two patients with benign disease had negative scans. Comparison with conventional methods of scanning showed good correlation. The success of this pilot study should encourage the search for more tumour-specific antigens and further study of the implications for treatment.